China in Malaysia State-Business Relations and the New Order of Investment Flows - Gomez, Edmund Terence; Tham, Siew Yean; Li, Ran; Cheong, Kee Cheok (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2020)
XIX, 116 p. 5 illus., 3 illus. in color.